The Role of Cyber-Creation in Da'wah for the Development of Urban Muslim Communities - Siti Nuri Nurhaidah; Nabila Lubis; Hidayatullah (Universitas Negeri Jakarta, 2025)
This study aims to analyze the concept of cyber-creation in Islamic preaching within the framework of digital literacy, focusing on the development of Muslim communities in urban areas. Using a qualitative approach through literature review and digital content analysis, this research identifies strategies, techniques, and communication patterns in digital da'wah via social media, online video platforms, and interactive da'wah websites. Thematic analysis reveals that cyber-creation, as a creative process in producing and distributing da'wah content, enhances audience engagement, expands the reach of Islamic messages, and encourages inclusive religious dialogue. Effective strategies include visual storytelling, context-based approaches on social issues, and two-way interaction with audiences. Da'wah practitioners also leverage social media algorithms to target specific audience segments. Challenges include low digital literacy among preachers and the risk of disseminating inaccurate religious content. Nonetheless, this opens opportunities for strengthening religious literacy and forming participatory digital communities. This study contributes to the advancement of contemporary Islamic preaching in the digital era.